Service needs of children with disabilities in Jamaica - Thorburn, Marigold J. (1992)
This study investigated the service needs of 994 2- to 9-year-old children in Clarendon, Jamaica. Parents were asked about symptoms relating to six different disabilities--visual, hearing, speech, motor, cognitive, and fits. Following medical and psychological assessment, a diagnosis of mild, moderate, severe, or no disability was made. For children with disabilities, the frequencies of five possible types of intervention recommended by the physician were analysed and related to the prevalence of the six disabilities in the parish. Of the disabled children, 62 percent needed special education, 29.5 percent needed community-based services, 21 percent needed spectacles, 21 percent needed specialist referral, and 6 percent required medical treatment. Training of existing health and education personnel in basic techniques of screening and assessment was recommended
Keywords: Disabled children